The Treatment of Activated PI3Kδ Syndrome - Coulter, Tanya I.; Cant, Andrew J. (Frontiers in Immunology, 2018)
Activated phosphoinositide 3-kinase δ syndrome (APDS), also known as PASLI disease (p110d-activating mutation causing senescent T cells, lymphadenopathy, and immunodeficiency) are combined immunodeficiencies resulting from gain-of-function mutations in the genes (PIK3CD and PIK3R1) encoding the subunits of phosphoinositide 3-kinase δ (PI3Kδ) and were first described in 2013. These mutations result in the hyperactivation of the PI3K/AKT/mTOR/S6K signally pathways. In this mini-review we have detailed the current treatment options for APDS. These treatments including conventional immunodeficiency therapies such as immunoglobulin replacement, antibiotic prophylaxis and hematopoietic stem cell transplant. We also discuss the more targeted therapies of mTOR inhibition with sirolimus and selective PI3Kδ inhibitors.